DnaB helicase dynamics in bacterial DNA replication resolved by single-molecule studies. Issue 12 (17th June 2021) - Spinks, Richard R; Spenkelink, Lisanne M; Stratmann, Sarah A; Xu, Zhi-Qiang; Stamford, N Patrick J; Brown, Susan E; Dixon, Nicholas E; Jergic, Slobodan; van Oijen, Antoine M
Abstract: In Escherichia coli, the DnaB helicase forms the basis for the assembly of the DNA replication complex. The stability of DnaB at the replication fork is likely important for successful replication initiation and progression. Single-molecule experiments have significantly changed the classical model of highly stable replication machines by showing that components exchange with free molecules from the environment. However, due to technical limitations, accurate assessments of DnaB stability in the context of replication are lacking. Using in vitro fluorescence single-molecule imaging, we visualise DnaB loaded on forked DNA templates. That these helicases are highly stable at replication forks, indicated by their observed dwell time of ∼30 min. Addition of the remaining replication factors results in a single DnaB helicase integrated as part of an active replisome. In contrast to the dynamic behaviour of other replisome components, DnaB is maintained within the replisome for the entirety of the replication process. Interestingly, we observe a transient interaction of additional helicases with the replication fork. This interaction is dependent on the τ subunit of the clamp-loader complex. Collectively, our single-molecule observations solidify the role of the DnaB helicase as the stable anchor of the replisome, but also reveal its capacity for dynamic interactions. Graphical Abstract: